A high-entropy energy storage ceramic composition suitable for base metal electrodes and a method of making the same
Patent Information
- Application Number
- CN202611367462.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-27
AI Technical Summary
这些方案在一定程度上实现了贱金属化,但其主相仍主要围绕BaTiO3或常规Ba(Zr,Ti)O3展开,A位组分元素单一或近单一,局域结构无序度和构型熵不足,难以充分拉平介电温谱、抑制晶粒异常长大并提高击穿一致性
[0035](1)通过A位多元占位与B位双元调控,实现宽温区介电稳定性与高储能密度的统一。
Smart Images

Figure CN122991855A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy storage ceramics technology, specifically to a high-entropy energy storage ceramic composition suitable for base metal electrodes and its preparation method. Background Technology
[0002] Pulse energy storage ceramic capacitors are passive electronic components capable of storing and releasing electrical energy in an extremely short time. They feature high power density, fast charge and discharge speeds, long cycle life, good temperature stability, and high reliability, and are widely used in pulse power supplies, laser power supplies, medical equipment, new energy vehicles, power electronics, ignition circuits, strobe lights, and pulsed lighting. Compared to film capacitors, ceramic capacitors offer significant advantages in miniaturization, high voltage withstand, low dielectric loss, and high reliability, making them an indispensable key component in pulse power systems.
[0003] However, optimizing the performance of pulse energy storage ceramic materials faces significant technical challenges. Specifically, there is often an inverse relationship between the dielectric constant, breakdown strength, temperature stability, and adaptability to reducing atmospheres of ceramic materials. Simply increasing the dielectric constant often leads to increased dielectric loss, decreased insulation resistance, or reduced breakdown strength, making it difficult to simultaneously meet the application requirements of high energy density, high reliability, and wide temperature stability.
[0004] Currently, the mainstream pulse energy storage ceramic powder on the market is represented by LF451C powder from Ferro Corporation of the United States. Although this system has excellent electrical performance, it needs to be used with precious metal electrodes such as silver and palladium, which results in high electrode material costs and seriously restricts the large-scale domestic substitution and industrialization of high-capacity, high-reliability pulse energy storage ceramic capacitors.
[0005] To reduce electrode costs, some existing technologies attempt to use base metal electrodes such as nickel, with BaTiO3 or Ba(Zr,Ti)O3 as the main crystalline phase. By adding certain metal elements and glassy phases as byproducts, their adaptability, dielectric loss, insulation resistance, and temperature stability under reducing atmosphere sintering conditions are improved. These solutions achieve base metalification to a certain extent, but their main phase still revolves primarily around BaTiO3 or conventional Ba(Zr,Ti)O3. The A-site composition is single or nearly single, resulting in insufficient local structural disorder and configuration entropy, making it difficult to sufficiently flatten the dielectric temperature spectrum, suppress abnormal grain growth, and improve breakdown uniformity. Furthermore, existing modification methods mostly focus on B-site substitution, with limited research on multi-element synergistic regulation at the A-site, leading to limited improvement in temperature stability and making it difficult to meet stringent requirements.
[0006] In summary, how to enable pulse energy storage ceramics to simultaneously possess high dielectric constant, low loss, high insulation resistance, high breakdown strength, and excellent temperature stability through innovative main phase structure and synergistic control of defect chemistry under reducing atmosphere sintering conditions suitable for base metal electrodes has become a pressing technical challenge in this field. Summary of the Invention
[0007] The present invention aims to provide a high-entropy energy storage ceramic composition suitable for base metal electrodes and its preparation method. The main component of the ceramic composition, the perovskite structure, can improve the configurational entropy and local structural disorder of the perovskite main phase by controlling the ternary mixing of Ba / Ca / Sr at the A site and the Zr / Ti ratio at the B site. The defect chemistry under the reducing atmosphere is controlled by the secondary components of Gd, Mg, and Mn. The densification and grain boundary insulation are improved by a small amount of glass phases such as BaO-CaO-SiO2, thereby achieving a high dielectric constant, low loss, high insulation, high breakdown and temperature stability in a low-cost base metal electrode system.
[0008] To achieve the above objectives, the present invention proposes the following technical solution:
[0009] A high-entropy energy storage ceramic composition suitable for base metal electrodes, comprising a main component and a secondary component;
[0010] The main component is a high-entropy solid solution with a perovskite structure, and its general formula is: (Ba a Ca b Sr c (Zr) x Ti 1-x O3;
[0011] Where a+b+c=1, 0.20≤a≤0.45, 0.20≤b≤0.45, 0.20≤c≤0.45, 0.15≤x≤0.50; and the total configuration entropy of the principal components is greater than or equal to 1.5R, where R is the gas constant;
[0012] The secondary components include a first secondary component Gd, a second secondary component Mg, and a third secondary component Mn;
[0013] Based on a total of 100 molar parts of the main component A-site cations Ba+Ca+Sr, the Gd element is 2-12 molar parts, the Mg element is 0.5-5 molar parts, and the Mn element is 0.05-2 molar parts.
[0014] As a preferred technical solution of the present invention, the general formula (Ba a Ca b Sr c (Zr) x Ti 1-x In O3:
[0015] 0.30≤a≤0.40, 0.25≤b≤0.40, 0.25≤c≤0.40, 0.20≤x≤0.35.
[0016] As a preferred embodiment of the present invention, a=b=c=1 / 3, x=1 / 3.
[0017] As a preferred embodiment of the present invention, based on a total of 100 molar parts of the main component A-site cations Ba+Ca+Sr, the Gd element is 3-8 molar parts, the Mg element is 1-3 molar parts, and the Mn element is 0.1-1 molar parts.
[0018] As a preferred embodiment of the present invention, the secondary component further includes a fourth secondary component, a glass phase, and the amount of the glass phase is 0.2 to 5 parts by mass based on 100 parts by mass of the main component powder.
[0019] The glass phase is selected from one or more of the Ba-B-Si system, Ba-B-Si-Al system, Li-Al-Ti-Si system, or Ba-Ca-Si system.
[0020] As a preferred embodiment of the present invention, the amount of the glass phase is 0.2 to 3 parts by mass, based on 100 parts by mass of the main component powder.
[0021] As a preferred embodiment of the present invention, Gd may be partially or completely replaced by one or more of Y, Dy, Ho, Er, Yb, La, Nd, and Sm.
[0022] This invention also provides a method for preparing a high-entropy energy storage ceramic composition suitable for base metal electrodes, comprising the following steps:
[0023] (1) Weigh the main component raw materials and auxiliary component raw materials according to the design ratio. The main component raw materials include compounds that provide A-site cations Ba, Ca, and Sr, and compounds that provide B-site cations Ti and Zr. The auxiliary component raw materials include compounds that provide Gd, compounds that provide Mg, and compounds that provide Mn.
[0024] When it is necessary to add the glass phase, the glass phase powder is also weighed out;
[0025] (2) Place the weighed raw materials in a dispersion medium and mix them by wet ball milling or sand milling;
[0026] (3) After drying, pre-calcined at 1050-1200℃ for 1-4 hours to form a high-entropy perovskite solid solution;
[0027] (4) The pre-calcined powder is ball-milled twice, a binder is added, and then dried and granulated;
[0028] (5) The granulated powder is shaped into a green body;
[0029] (6) Degumming;
[0030] (7) Sintering is carried out in a reducing atmosphere at 1180-1230℃ for 1-4 hours;
[0031] (8) Under the condition that the oxygen partial pressure is higher than the reducing atmosphere of step (7), the re-oxidation treatment is carried out at 800-1050°C for 0.5-4 hours.
[0032] As a preferred technical solution of the present invention, the reducing atmosphere in step (7) is N2-H2-H2O or N2-H2 mixture, and its oxygen partial pressure matches the Ni / NiO equilibrium oxygen partial pressure.
[0033] As a preferred technical solution of the present invention, the molding in step (5) is dry pressing, casting, lamination or isostatic pressing.
[0034] As can be seen from the above technical solutions, the technical solution of the present invention provides a high-entropy energy storage ceramic composition suitable for base metal electrodes and its preparation method. Compared with the prior art, the present invention achieves a systematic breakthrough in the comprehensive performance of pulse energy storage ceramics under the co-firing conditions of base metal electrodes through a triple synergistic strategy of "high-entropy main phase, defect chemistry, and glass phase". Its beneficial effects are specifically reflected in the following aspects.
[0035] (1) By using multi-occupancy of position A and dual-element regulation of position B, the dielectric stability of wide temperature range and high energy storage density are achieved.
[0036] This invention features a high-entropy perovskite as the main phase, characterized by disordered ternary Ba / Ca / Sr sites at A-sites and binary Zr / Ti sites at B-sites. The total configurational entropy can reach 1.59R to 1.74R, satisfying the configurational entropy criterion for high-entropy ceramics. 2+ Ca 2+ 、Sr 2+ Three types of A-site ions with different radii are randomly distributed, forming a non-uniform strain field and local polarization differences in the crystal lattice. This effectively disrupts the long-range ferroelectric order of traditional BaTiO3-based ferroelectrics, broadening the Curie temperature from a sharp single phase transition peak to a diffuse dielectric temperature spectrum. Simultaneously, B-site Zr... 4+ For Ti 4+Partial substitution further dilutes the ferroelectric coupling strength, introducing polar nanoregions. Under the preferred composition window (A-site Sr molar fraction ≥ 0.30, Ba molar fraction ≤ 0.38, B-site Zr molar fraction ≥ 0.30), the absolute value of the capacity change rate of the ceramic over the entire temperature range of -55℃ to 125℃ can be controlled within the range that meets the EIA X7T grade requirements. In contrast, existing BaTiO3-based or conventional Ba(Zr,Ti)O3-based energy storage ceramics often exhibit a capacity change rate exceeding -30% at 125℃ under the same dielectric constant level, making it difficult to meet the X7T wide-temperature stability requirements. The high-entropy strategy of this invention significantly widens the operating temperature range without significantly sacrificing the dielectric constant, breaking the conventional constraint relationship between dielectric constant and temperature stability.
[0037] (2) Through high-entropy thermodynamic effects and hysteresis diffusion mechanism, the breakdown field strength and pulse cycle reliability are significantly improved.
[0038] The high-entropy main phase of this invention, with its multi-ion co-occupancy structure, endows the system with high configurational entropy and thermodynamic stability, reduces the system's free energy, suppresses the tendency for second-phase precipitation during cooling, and ensures that the main phase is a single or near-single perovskite solid solution, reducing local electric field concentration and breakdown weak points caused by the second phase. More importantly, the hysteresis diffusion effect in the high-entropy system effectively suppresses abnormal grain growth during sintering, resulting in a more uniform and fine grain size distribution and a denser microstructure, thereby reducing structural defects and charge trap density at grain boundaries. The uniform and fine-grained structure also implies better pulse cycle stability and lifetime reliability, which is of great significance for high-frequency charge and discharge scenarios such as pulsed power supplies and laser power supplies. In addition, the chemical homogeneity of the high-entropy main phase makes the dielectric response of each micro-region tend to be consistent, further improving the capacitance consistency and yield of capacitor devices, which is beneficial for large-scale industrial production.
[0039] (3) High insulation and low loss characteristics under reducing atmosphere sintering are achieved through the chemical synergy of Gd-Mg-Mn ternary defects.
[0040] In this invention, Gd 3+ It can replace Ti in a reducing atmosphere 4+ (B site), inhibiting Ti 4+ Transform into Ti 3+ The reduction process reduces the generation of electron carriers at the source; at the same time, Gd 3+Mg forms defect association pairs with oxygen vacancies, pinning oxygen vacancy migration and reducing leakage current. Mg, together with Gd / Mn and the re-oxidation process, regulates the concentration, valence compensation, and migration of oxygen vacancies, and inhibits anomalous grain growth. Mn ions accumulate at grain boundaries and grain surfaces, acting as electron traps and providing additional capture channels for residual free electrons not completely suppressed by Gd. The synergistic effect of these three factors enables the ceramic of this invention to maintain extremely high insulation resistance and low dielectric loss after sintering in a reducing atmosphere, fully meeting the stringent requirements of MLCCs for high insulation and low loss in the dielectric layer.
[0041] (4) By optimizing the sintering behavior through the glass phase, the process window for co-firing base metal electrodes is broadened.
[0042] This invention introduces an appropriate amount of Ba-Ca-Si or Ba-B-Si glass phase, forming a trace liquid phase during sintering, which has three positive effects. First, the liquid phase promotes particle rearrangement and mass transport, reducing the densification temperature from the conventional 1250℃ or higher to 1180℃, achieving a better match with the melting point and thermal expansion coefficient of the nickel electrode, effectively avoiding the problems of spheroidization, delamination, or diffusion into the dielectric layer of the nickel electrode during high-temperature sintering. Second, the glass phase fills grain boundary pores, reducing microcracks and voids, improving the density of the ceramic body, and directly contributing to the improvement of the breakdown field strength. Third, the glass phase forms a high-resistivity insulating layer at the grain boundaries, constructing a grain boundary barrier, further improving IR and withstand voltage capabilities. The reasonable amount of glass phase makes the sintering temperature range of this invention have good tolerance to temperature fluctuations in industrial kilns, significantly improving product consistency and yield, and facilitating industrialization.
[0043] (5) A systematic breakthrough in comprehensive performance is achieved through the triple synergy of "high-entropy main phase - defect chemistry - glass phase".
[0044] The most prominent advantage of this invention lies in the organic integration of three techniques: high-entropy main phase design, Gd-Mg-Mn defect chemical regulation, and glass-phase-assisted sintering, rather than a simple combination of elements. The synergistic effect among these three techniques results in a systemic performance breakthrough that transcends any single element: the high-entropy main phase provides a platform foundation for wide-temperature stability and a uniform fine-grained structure; Gd-Mg-Mn maximizes defect chemical regulation efficiency on this platform, achieving high insulation and low loss under a reducing atmosphere; and the glass phase further enhances grain boundary insulation and density while lowering the sintering temperature. This synergy enables the ceramic composition of this invention to achieve an excellent balance across the five core performance dimensions: dielectric constant, loss, temperature stability, insulation resistance, and breakdown strength. Existing technologies typically optimize only two or three of these dimensions, making it difficult to address all aspects simultaneously.
[0045] (6) Significant economic benefits and industrialization value.
[0046] The main phase raw materials and by-products of this invention are all common industrial raw materials, widely available and inexpensive, and do not require the use of harmful elements such as lead, thus meeting environmental protection requirements. More importantly, the ceramic composition of this invention can be co-fired with base metal electrodes such as nickel in a reducing atmosphere, completely eliminating dependence on precious metal electrodes such as silver and palladium. Electrode material costs can be reduced by 60% to 80%, and the preparation process is highly compatible with existing MLCC production lines, requiring no large-scale equipment modifications, thus possessing strong industrial transformation feasibility and market competitiveness. In summary, the ceramic composition and its preparation method provided by this invention have broad application prospects in application fields with stringent requirements for energy storage density, temperature stability, and reliability, such as pulsed power supplies, laser power supplies, medical equipment, new energy vehicles, and power electronics. It is of significant strategic importance for promoting the domestic substitution and technological upgrading of high-performance base metal electrode MLCCs.
[0047] It should be understood that all combinations of the foregoing concepts and the additional concepts described in more detail below can be considered part of the inventive subject matter of this disclosure, provided that such concepts do not contradict each other.
[0048] The foregoing and other aspects, embodiments, and features of the teachings of the present invention will be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the invention, such as features and / or beneficial effects of exemplary embodiments, will become apparent from the following description or may be learned through practice of specific embodiments according to the teachings of the present invention. Attached Figure Description
[0049] The accompanying drawings are not drawn to scale. In the drawings, each identical or nearly identical component shown in the various figures may be denoted by the same reference numeral. For clarity, not every component is labeled in each figure. Embodiments of various aspects of the invention will now be described by way of example and with reference to the accompanying drawings, wherein:
[0050] Figure 1 This is a TCC curve diagram of Embodiment 5 of the present invention;
[0051] Figure 2 This is a TCC curve diagram of Embodiment 8 of the present invention;
[0052] Figure 3 This is a TCC curve diagram of Embodiment 10 of the present invention; Detailed Implementation
[0053] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.
[0054] The terms "first," "second," and similar words used in the specification and claims of this patent application do not indicate any order, quantity, or importance, but are merely used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "an," "a," or "the," etc., do not indicate a quantity limitation, but rather indicate the presence of at least one. Terms such as "comprising" or "including" mean that the element or object preceding "comprising" encompasses the features, wholes, steps, operations, elements, and / or components listed following "comprising" or "including," and do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components, and / or collections thereof. Terms such as "upper," "lower," "left," and "right" are used only to indicate relative positional relationships; when the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0055] This invention provides a high-entropy energy storage ceramic composition suitable for base metal electrodes, comprising a main component and several secondary components. The main component (also referred to as the main phase) is a high-entropy perovskite compound with the general formula: (Ba a Ca b Sr c (Zr) x Ti 1-x )O3.
[0056] Where a represents the mole fraction of Ba at site A, 0.20≤a≤0.45; b represents the mole fraction of Ca at site A, 0.20≤b≤0.45; c represents the mole fraction of Sr at site A, 0.20≤c≤0.45; and a+b+c=1; x represents the mole fraction of Zr at site B, 0.15≤x≤0.50; and correspondingly, (1-x) represents the mole fraction of Ti at site B.
[0057] In some preferred embodiments of the present invention, the principal component formula (Ba a Ca b Sr c (Zr) x Ti1-x In O3, 0.30≤a≤0.40, 0.25≤b≤0.40, 0.25≤c≤0.40, and satisfy a+b+c=1; 0.20≤x≤0.35.
[0058] More preferably, if a=b=c=1 / 3 and x=1 / 3, then the structural formula of the principal component is: (Ba 1 / 3 Ca 1 / 3 Sr 1 / 3 (Zr) 1 / 3 Ti 2 / 3 )O3.
[0059] In this invention, "high entropy" refers to the fact that the A-site and / or B-site in the main component perovskite structure are randomly occupied by multiple element ions, and its configuration entropy satisfies S conf ≥1.5R, where R is the gas constant, R=8.314 J / (mol·K).
[0060] The formula for calculating configuration entropy is S = -RΣx i ln x i , where x i The mole fraction of each component in the corresponding cationic sublattice is given, and the total configuration entropy is the sum of the configuration entropies of the A-site and the B-site.
[0061] According to the present invention, the perovskite ABO3 structure is calculated and summed for the A-site and B-site respectively.
[0062] For a more preferred principal component structure (Ba 1 / 3 Ca 1 / 3 Sr 1 / 3 (Zr) 1 / 3 Ti 2 / 3 The configurational entropy of O3 at site A is:
[0063] S A = -R[1 / 3 ln(1 / 3) + 1 / 3 ln(1 / 3) + 1 / 3 ln(1 / 3)] = 1.0986R.
[0064] The configuration entropy of position B is:
[0065] S B = -R[1 / 3 ln(1 / 3) + 2 / 3 ln(2 / 3)] = 0.6365R.
[0066] Therefore, the preferred total configuration entropy of the principal components in this invention is: S conf = 1.0986R + 0.6365R = 1.7351R.
[0067] According to the commonly used S in high-entropy ceramics confAccording to the ≥1.5R criterion, the preferred main phase satisfies the configuration entropy requirement of high-entropy perovskite materials.
[0068] As can be seen from the above principal component structure, it has a high-entropy perovskite structure with equimolar mixture of Ba, Ca and Sr at the A site and dual-element control of Zr and Ti at the B site. The elements at the A site and the elements at the B site have a clear cooperative division of labor.
[0069] Specifically, Ba 2+ Larger ionic radii and higher polarizability are beneficial for maintaining a higher dielectric constant; Ca 2+ The small ionic radius of Sr leads to localized lattice distortion upon introduction, which helps to modulate dielectric temperature characteristics and suppress low-frequency dielectric relaxation; 2+ Ions can effectively lower the Curie temperature of the system and broaden the dielectric temperature peak towards room temperature, thus keeping the dielectric constant relatively flat over a wide temperature range; Zr 4+ The introduction of Ti can break Ti 4+ -O - Ti 4+ Long-range ferroelectric ordering forms nanoscale polar microregions, enhancing dispersed phase transition behavior, thereby increasing the breakdown field strength and reducing the temperature dependence of the dielectric constant; Ti 4+ This provides the main displacement polarization contribution, ensuring that the dielectric constant remains at a high level. The cooperative random occupancy of these pentagonal ions at the A / B sites, through the superposition of the local strain field and the charge fluctuations generated by heterovalent doping such as Gd / Mg / Mn, enables the system to exhibit a broadened dielectric response and suppressed long-range order.
[0070] Within the scope of the technical concept of this invention, the ratio of Ba, Ca, and Sr at the A-site can be adjusted within the above-mentioned range, but it is necessary to ensure that all three elements participate in site occupancy at the A-site to avoid degenerating into a binary or single perovskite system, which would lead to insufficient configuration entropy and sharpening of the dielectric temperature spectrum. The ratio of Zr and Ti at the B-site can also be adjusted within the above-mentioned range: when the Zr ratio is too low (x < 0.15), the long-range ferroelectric order is not sufficiently destroyed, the Curie peak is sharp, and the TCC index is prone to exceed the limit; when the Zr ratio is too high (x > 0.50), the system is excessively diluted, the dielectric constant decreases significantly, and the energy storage density decreases. Preferably, the mole fraction x of Zr is controlled between 0.20 and 0.35, then the mole fraction (1-x) of Ti corresponds to 0.80 to 0.65.
[0071] Based on 100 molar parts of the total amount of the main component A-site cations (Ba+Ca+Sr), the ceramic composition also contains the following secondary components:
[0072] The first secondary component, Gd, is 2–12 molars, preferably 3–8 molars. The preferred source of Gd is Gd₂O₃. 3+ The perovskite structure exhibits amphoteric A / B site occupancy characteristics: under reducing atmosphere sintering conditions, Gd3+ Prefers to occupy B sites (Ti sites), suppressing Ti through donor doping. 4+ Restored to Ti 3+ The generated electrons conduct electricity, significantly increasing the insulation resistance; at the same time, Gd 3+ It forms defect association pairs with oxygen vacancies, effectively pinning oxygen vacancy migration and reducing dielectric loss and leakage current.
[0073] In other specific embodiments, Gd can be partially or completely replaced by one or more rare earth elements selected from Y, Dy, Ho, Er, Yb, La, Nd, and Sm. After replacement, the donor doping effect and insulation improvement effect under a reducing atmosphere should be maintained, and a second phase with significant rare earth enrichment should not be formed. When the above-mentioned substitute rare earth elements are used, their amount is still based on elemental molar parts, and the range is the same as that of Gd element.
[0074] The second component, Mg, is 0.5 to 5 moles, preferably 1 to 3 moles. The preferred source of Mg is MgO, MgCO3, or compounds that can be calcined into MgO, such as magnesium acetate or magnesium nitrate, but the introduction of residual impurity anions should be avoided.
[0075] Mg 2+ In the perovskite structure, Mg primarily occupies B sites. As an acceptor dopant, its core functions include: reducing oxygen vacancy concentration, inhibiting abnormal grain growth, making the microstructure more uniform and dense, and reducing breakdown weaknesses; 2+ The smaller ionic radius causes local lattice contraction, which can fine-tune the Curie temperature and dielectric relaxation behavior, reducing dielectric loss. When MgCO3 or other materials are used to replace magnesium sources, the effective doping amount is ensured to remain unchanged by equivalent molar fractions of Mg.
[0076] The third sub-component, Mn, is 0.05 to 2 moles, preferably 0.1 to 1 mole. The preferred source of Mn is MnCO3, MnO, MnO2, or other manganese salts that can be calcined into manganese oxides.
[0077] Mn has a variable valence state (Mn 2+ / Mn 3+ / Mn 4+ In reducing atmosphere sintering, Mn ions can act as "electron traps." Specifically, Mn ions accumulate at grain boundaries and grain surfaces, trapping free electrons and effectively alleviating the effects of Ti ion depletion. 4+ The electronic conductivity that may result from reduction forms a "donor-acceptor" synergistic defect compensation mechanism with Gd, significantly reducing dielectric loss and improving insulation reliability. When MnO or MnO2 is used to replace MnCO3, the conversion is based on the equivalent molar fraction of Mn.
[0078] The Gd-Mg-Mn ternary synergistic mechanism: Gd donor doping suppresses electronic conductivity, Mg acceptor doping reduces oxygen vacancy concentration and suppresses abnormal grain growth, and Mn's variable valence state provides additional electron trapping channels. The synergistic effect of the three covers the complete defect chemical regulation chain from "carrier source suppression" (Mg), "carrier trapping elimination" (Mn) to "carrier generation suppression" (Gd). This is the key guarantee for achieving high insulation resistance, low loss and high breakdown reliability simultaneously under reducing atmosphere (co-firing conditions of nickel electrode).
[0079] The ceramic composition also contains a glass phase as a fourth component, which is used to promote liquid phase sintering densification, reduce sintering temperature, and optimize grain boundary insulation properties.
[0080] Based on 100 parts by weight of the main component powder, the amount of glass phase is 0 to 5 parts by weight, preferably 0.2 to 3 parts by weight. The glass phase is selected from one or more of the Ba-B-Si system, Ba-B-Si-Al system, Li-Al-Ti-Si system, or Ba-Ca-Si system.
[0081] The mechanism of the glass phase is as follows: during sintering, it forms a suitable amount of liquid phase, wets the grain boundaries and fills the pores, promoting the densification process of the ceramic body and reducing the sintering temperature from the conventional 1250℃ or higher to 1180-1230℃. This ensures a good match with the melting point (1455℃) and thermal expansion coefficient of the nickel electrode, preventing electrode spheroidization and delamination. Simultaneously, after cooling, the glass phase forms a high-resistivity glass layer at the grain boundaries, creating a grain boundary insulating barrier and further improving the breakdown field strength. However, it is important to note that the amount of glass phase should not exceed 5 parts by mass; otherwise, excessive low-melting-point glass phase will form a continuous grain boundary layer, leading to a significant decrease in dielectric constant, an increase in dielectric loss, and a reduction in breakdown strength. In the preferred embodiment, when the amount of glass phase is controlled at 0.5-1.5 parts by mass, an optimal balance can be achieved between densification, breakdown strength, and dielectric constant.
[0082] Therefore, in this application, the high-entropy main crystalline phase is responsible for "flattening the dielectric temperature spectrum, stabilizing the perovskite structure, and improving the uniformity of grain and phase composition"; Gd-Mg-Mn is responsible for "defect compensation and electronic conductivity suppression under reducing atmosphere"; and the glassy phase is responsible for "low-temperature densification and grain boundary insulation regulation". The synergy of these three phases enables the simultaneous achievement of high dielectric constant, low tanδ, high insulation resistance, high breakdown strength, and X7T temperature stability under base metal electrode reduction sintering conditions.
[0083] The present invention also provides a method for preparing the above-mentioned ceramic composition, comprising the following steps:
[0084] (1) Weigh each raw material according to the proportion, including carbonates of Ba, Ca and Sr, such as BaCO3, CaCO3 and SrCO3; oxides of Ti and Zr, such as TiO2 and ZrO2; as well as Gd2O3, MgO, MnCO3 and glass phase powder.
[0085] (2) Using anhydrous ethanol, isopropanol or deionized water as the medium, wet ball milling or sand milling with zirconia balls for 4 to 24 hours is carried out to fully mix the components and obtain the mixture.
[0086] (3) After drying the mixture, pre-calcining it at 1050-1200℃ for 1-4 hours to obtain pre-calcined powder. Pre-calcination promotes the random occupation of Ba, Ca, and Sr at site A and random occupation of Zr and Ti at site B, forming a single or near-single high-entropy perovskite solid solution.
[0087] (4) The pre-calcined powder is ball-milled to the target particle size, and a binder, such as polyvinyl alcohol (PVA), polyvinyl butyral (PVB) or acrylic resin, is added. The powder is then dried and granulated to obtain granules.
[0088] (5) The granules are dry-pressed to form green bodies, wherein the pressing pressure is 0.5 to 2 T / cm. 2 1T / cm is preferred 2 .
[0089] In other specific embodiments, MLCC green blanks can also be prepared by tape casting, stacking, and isostatic pressing.
[0090] (6) Slowly heat up and remove the binder in air, nitrogen, or a weak oxidizing atmosphere to remove the organic binder. Removing the binder in air, nitrogen, or a weak oxidizing atmosphere can, on the one hand, reduce the oxygen partial pressure to slow down the oxidation and combustion rate of the organic binder and prevent cracking of the green body due to local overheating; on the other hand, it can provide sufficient oxygen potential to completely oxidize the organic matter into gaseous products and escape, avoiding carbon residue; at the same time, it can prevent the nickel electrode from oxidizing too early at this stage, and provide a good electrode / dielectric interface state for subsequent co-firing in a reducing atmosphere.
[0091] (7) Sintering is carried out in a reducing atmosphere at 1180–1230℃ for 1–4 hours. The reducing atmosphere is N2-H2-H2O or a N2-H2 mixture, and its oxygen partial pressure should match the stability window of the nickel electrode, that is, match the Ni / NiO equilibrium oxygen partial pressure, to ensure that the nickel electrode is neither oxidized nor excessively reduced. Specifically, the Ni / NiO equilibrium oxygen partial pressure is approximately 1 × 10⁻⁶. −8 ~4×10 −8 atm.
[0092] (8) Under the reducing atmosphere conditions where the oxygen partial pressure is higher than that in step 7, the re-oxidation treatment is carried out at 800-1050℃ for 0.5-4 hours to moderately re-oxidize the grain boundaries and near-surface areas, reduce the excess oxygen vacancies and electronic conductivity generated by reduction sintering, and further improve the insulation resistance.
[0093] (9) Electrode preparation and testing are carried out after sintering.
[0094] The core of this invention is not simply the mechanical mixing of raw materials such as BaCO3, CaCO3, SrCO3, TiO2, and ZrO2, but rather the formation of a high-entropy perovskite solid solution through pre-calcination and sintering, which allows Ba, Ca, and Sr to randomly occupy sites at A-sites, and Zr and Ti to randomly occupy sites at B-sites. This main phase possesses high configurational entropy, strong local distortion, and a wide local Curie temperature distribution, thereby improving the temperature stability and breakdown consistency of conventional BZT systems.
[0095] The present invention also provides multilayer ceramic capacitors and pulse energy storage ceramic capacitors made from the above-described ceramic composition. The ceramic composition is particularly suitable for co-firing with base metal electrodes such as nickel to manufacture high-capacity, high-reliability, and wide-temperature-stability base metal electrode multilayer ceramic capacitors.
[0096] The present invention will be further illustrated below through specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and do not constitute a limitation on the scope of the present invention.
[0097] The calculated configuration entropy results for sites A and B in each embodiment are shown in Table 1. As can be seen from Table 1, the total configuration entropy of all embodiments is ≥1.5R, which meets the criterion requirements for high-entropy ceramics.
[0098] Table 1 Configuration Entropy Calculation for Each Embodiment
[0099] In all embodiments, the raw materials used are BaCO3, CaCO3, SrCO3, TiO2, ZrO2, Gd2O3, MgO, MnCO3, and BaO-CaO-SiO2 glass. It should be noted that the amounts of each raw material in Table 2 are measured based on 1 mol of the main phase (i.e., ABO3, corresponding to a total A-site cation of 1 mol); the amount of the glass phase is based on 100 parts by mass of the main phase powder, with the unit being parts by mass. Except for the BaO-CaO-SiO2 glass phase system, which is in parts by mass, the units for all other components are in mol. The molar amounts of Gd, Mg, and Mn are converted according to elemental conversion. If Gd2O3, MgO, and MnCO3 are actually weighed, they should be converted to the equivalent molar amounts of the elements; the glass phase is controlled by parts by mass, not simply by mol.
[0100] Conversion rules: Number of moles of Gd2O3 (mol) = Moles of Gd element / 200; Number of moles of MgO (mol) = Moles of Mg element / 100; Number of moles of MnCO3 (mol) = Moles of Mn element / 100.
[0101] The specific raw material ratios for each embodiment are shown in Table 2.
[0102] Table 2 Raw material ratios for each embodiment
[0103] Each embodiment prepared its respective sample according to the following steps:
[0104] (1) Weigh each raw material according to the proportions in Table 2.
[0105] (2) Using anhydrous ethanol as the medium, wet ball milling was performed using zirconia balls for 12 hours.
[0106] (3) After drying, pre-calcine at 1100℃ for 2 hours.
[0107] (4) The pre-calcined powder is ball-milled twice, PVA binder is added, and then dried and granulated.
[0108] (5) Dry pressing, with a pressure of 1 T / cm 2 .
[0109] (6) Slowly heat up the air to remove the glue.
[0110] (7) Sintering is carried out in a N2-H2 reducing atmosphere at 1180-1230℃ for 2 hours.
[0111] (8) Perform re-oxidation treatment by holding at 900℃ and high oxygen partial pressure for 1 hour.
[0112] The ceramic samples prepared in the above embodiments were subjected to electrical performance tests. The test conditions and the meanings of the symbols in the table are as follows: the relative permittivity εr and dielectric loss tangent tanδ were measured using an LCR meter at room temperature (25℃) and frequency (1kHz); the capacitance temperature change rate (TCC) was tested at -55℃ and 125℃, and the capacitance value at 25℃ was used as the benchmark for calculation; the insulation resistance IR was tested at room temperature and DC voltage of 100V; the breakdown field strength was obtained by DC withstand voltage testing, and the sample thickness was approximately 0.15mm; the energy storage density W was calculated from the breakdown field strength and the dielectric constant. The test results of each embodiment are detailed in Table 3.
[0113] The electrical properties of the ceramic samples prepared in each embodiment were tested, and the results are shown in Table 3.
[0114] Table 3 Electrical properties of ceramic samples from each embodiment
[0115] As can be seen from Table 3, due to differences in component design, the various embodiments exhibit different orientations in performance dimensions such as dielectric constant, loss, temperature stability, insulation resistance and breakdown field strength, providing targeted selection space for different application scenarios.
[0116] See Figures 1 to 3 The TCC curves for Examples 5, 8, and 10 are shown respectively. Figure 1 Among them, the TCC curve of Example 5 is the flattest, indicating that the composition design with Ca=0.40 at site A has a unique advantage in improving low-temperature stability. Figure 2 In Example 8, due to the high Ti content of 0.80, the room temperature dielectric constant reached 1700, but the temperature spectrum showed obvious high dielectric constant orientation characteristics. Figure 3 In Example 10, the TCC curve is relatively flat, which verifies the effectiveness of the high-entropy main phase composition in broadening the dielectric temperature spectrum.
[0117] Firstly, regarding the dielectric constant, Examples 3, 6, and 8 exhibit significantly higher dielectric constants than other schemes, with room-temperature relative dielectric constants reaching 1500, 1580, and 1700, respectively. Analysis of their composition reveals that these three examples share a common characteristic: a high barium content at the A-site and a low zirconium content at the B-site, corresponding to a high titanium content. Barium ions possess the largest ionic radius and the highest polarizability, providing the strongest contribution to displacement polarization; titanium ions exhibit stronger ferroelectric activity compared to zirconium ions, which is beneficial for maintaining a high dielectric constant. However, at the same time, the dielectric loss of Examples 3, 6 and 8 increased to 0.0052, 0.0058 and 0.0065, respectively, the capacitance temperature change rate at 125°C decreased to -28%, -30% and -36%, respectively, and the breakdown field strength decreased to 40 V / μm, 39 V / μm and 36 V / μm, respectively. This indicates that there is a significant inverse relationship between high dielectric constant and temperature stability and breakdown reliability. This approach is suitable for high capacitance scenarios at room temperature with low requirements for temperature drift and withstand voltage.
[0118] Secondly, in terms of breakdown field strength and energy storage density, Examples 4, 7, and 11 showed the best performance. Example 7, in particular, achieved a breakdown field strength of 60 V / μm and an energy storage density of 13.5 J / cm². 3 The breakdown field strength of Example 11 is 59 V / μm, and the energy storage density is 13.9 J / cm³. 3 The breakdown field strength of Example 4 is 58 V / μm, and the energy storage density is 13.4 J / cm³. 3The common design features of these three embodiments are a high strontium content at the A-site, all not less than 0.35%, while the barium content is controlled below 0.35%; and a zirconium content at the B-site, all reaching 0.33% to 0.35%. Strontium ions can effectively lower the Curie temperature of the system and broaden the dielectric peak towards room temperature, while reducing local polarization fluctuations, which is beneficial to improving the consistency of breakdown. The high zirconium content fully disrupts the long-range ferroelectric order of titanium-oxygen-titanium, forming high-density polar nanoregions, significantly reducing the ferroelectric coupling strength while maintaining a certain dielectric constant, thereby increasing the breakdown field strength. Furthermore, the gadolinium-magnesium-manganese doping levels in these three embodiments are all at a high level: in Example 7, gadolinium, magnesium, and manganese are 6.0 mol, 2.2 mol, and 0.45 mol, respectively; in Example 11, they are 6.5 mol, 2.2 mol, and 0.50 mol, respectively; and in Example 4, they are 5.5 mol, 2.0 mol, and 0.40 mol, respectively. Higher doping levels imply stronger donor-acceptor-trap synergistic defect control, which helps to maximally suppress electronic conductivity and oxygen vacancy migration under reducing atmosphere sintering conditions, thereby simultaneously achieving high insulation resistance and high breakdown strength. Therefore, if high energy density and high reliability are the goals, a combination of high strontium, high zirconium, and high doping should be prioritized.
[0119] Furthermore, regarding dielectric loss, the losses in Examples 7, 11, 9, and 4 are all controlled below 0.0030, with Example 7 having the lowest at 0.0025, Example 11 at 0.0026, Example 9 at 0.0029, and Example 4 at 0.0028. These low-loss examples also fall within the category of high strontium, high zirconium, and high doping, indicating a positive correlation between low loss and high breakdown. The physical mechanism lies in the fact that magnesium acceptor doping effectively reduces the oxygen vacancy concentration, manganese's variable valence state provides additional electron trapping channels, and gadolinium donor doping suppresses titanium ion reduction at the source. The synergistic effect of these three factors minimizes leakage current. For high-frequency charge-discharge or heat-sensitive pulsed applications, the above examples should be preferred.
[0120] Regarding temperature stability, according to the EIA standard, the X7T rating requires a mass change of +22% to -33% across the entire temperature range of -55℃ to 125℃. Based on the data in Table 3, the maximum absolute value of the drift across the entire temperature range for Examples 1, 2, 4, 7, 9, and 11 is less than or equal to 15%, fully meeting the X7T rating requirements. Examples 7 and 11 not only meet the X7T requirement but also exhibit a mass change of 13.5 J / cm³. 3The high energy storage density and extremely low loss (below 0.0027) described above represent the most technologically advanced aspects of this system. Examples 3, 6, 8, and 10 exhibit significant temperature drift at 125°C, making them suitable for limited temperature ranges. The examples satisfying X7T can be summarized in terms of composition as follows: Strontium molar fraction at A-site not less than 0.30, barium molar fraction not more than 0.38, and zirconium molar fraction at B-site not less than 0.30. Within this compositional window, the random localized strain field formed by the radii differences of the three ions at A-site and the dilution effect of zirconium on titanium at B-site together broaden the Curie peak into a diffuse phase transition, thus obtaining a smooth dielectric temperature spectrum.
[0121] Regarding the individual positioning of each embodiment, Example 1 serves as a baseline control, using equimolar A-site and B-site composition without adding a glass phase. This verifies the intrinsic properties of the basic high-entropy main phase under liquid-phase-free conditions, providing a comparative benchmark for subsequent additions of the glass phase. Example 2 introduces 0.5 parts by mass of glass phase based on Example 1, lowering the sintering temperature from 1210℃ to 1200℃, and increasing the dielectric constant from 1100 to 1220, demonstrating that trace amounts of glass phase can effectively improve density and dielectric constant without significantly sacrificing breakdown field strength. The composition of Example 10 is similar to that of Examples 1 and 2, aiming to verify the process repeatability of the optimal composition window. Its measured performance shows a gradient agreement with the former, indicating that the system has a good foundation for industrialization consistency.
[0122] Examples 3, 6, and 8 together constitute the direction of exploration for the upper limit of dielectric constant. The three examples gradually increased the barium content and decreased the zirconium content, eventually reaching the capacity ceiling of the system while maintaining basic formability and usability. However, they also clearly marked the failure boundary of this direction, that is, the temperature stability and breakdown reliability have been severely degraded to an unacceptable level within this window.
[0123] Examples 4, 7, and 11 collectively represent the optimization directions for breakdown strength and energy density. All three employ a strategy of high strontium, high zirconium, and high doping. Example 7 achieves the best breakdown field strength, Example 11 the best insulation resistance, and Example 4 achieves a relatively balanced trade-off between dielectric constant and breakdown strength. These three examples together demonstrate that the synergistic effect of a high-entropy main phase and enhanced defect chemistry is an effective technical path to achieving high energy density.
[0124] Example 5 was used to verify the effect of calcium on improving temperature stability. Its calcium content at site A was the highest in the entire table at 0.40. The measured capacity change rate at 125℃ was -21%, indicating that the local lattice distortion introduced by calcium ions does help pin domain walls and suppress temperature drift, but its improvement is not as great as the synergistic effect of zirconium and strontium.
[0125] Example 9, with its high strontium and moderate zirconium content, exhibits all performance indicators at the upper level of the table and meets the X7T standard, making it the recommended overall solution. This example fully demonstrates the existence of an optimal solution set in the multi-component composition space that is acceptable across all performance dimensions. For large-scale industrial production, this solution offers the best fault tolerance and mass production consistency.
[0126] Based on the above analysis, the embodiments can be categorized and positioned according to application scenarios as follows: For scenarios pursuing extremely high capacity, Embodiment 8, with its dielectric constant of 1700, is the preferred choice, but its higher losses and poorer temperature drift and withstand voltage must be accepted. For scenarios pursuing high pulse energy storage density and high reliability, Embodiments 7 and 11 are equally optimal, each with slight advantages in breakdown field strength and insulation resistance, respectively, and both have high energy storage density, making them the best overall performance solutions. For scenarios requiring stability over a wide temperature range, Embodiments 4 and 9 are both reliable choices. For industrial-scale mass production needs, Embodiment 9, with its characteristic of having no weaknesses in any of the five indicators, is the most suitable. Although Embodiment 7 has outstanding individual performance, its composition window is narrower, requiring higher precision in process control, making it suitable for high-end pulse energy storage capacitor products; Embodiment 9, on the other hand, has a wider window and better fault tolerance, making it more suitable for large-scale commercial promotion.
[0127] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A high-entropy energy storage ceramic composition suitable for base metal electrodes, characterized in that, It includes principal components and secondary components; The main component is a high-entropy solid solution with a perovskite structure, and its general formula is: (Ba a Ca b Sr c (Zr) x Ti 1-x O3; Where a+b+c=1, 0.20≤a≤0.45, 0.20≤b≤0.45, 0.20≤c≤0.45, 0.15≤x≤0.50; and the total configuration entropy of the principal components is greater than or equal to 1.5R, where R is the gas constant; The secondary components include a first secondary component Gd, a second secondary component Mg, and a third secondary component Mn; Based on a total of 100 molar parts of the main component A-site cations Ba+Ca+Sr, the Gd element is 2-12 molar parts, the Mg element is 0.5-5 molar parts, and the Mn element is 0.05-2 molar parts.
2. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 1, characterized in that, The general formula (Ba) a Ca b Sr c (Zr) x Ti 1-x In O3: 0.30≤a≤0.40, 0.25≤b≤0.40, 0.25≤c≤0.40, 0.20≤x≤0.
35.
3. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 2, characterized in that, a=b=c=1 / 3, x=1 / 3.
4. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 1, characterized in that, Based on a total of 100 molar parts of the main component A-site cations Ba+Ca+Sr, the Gd element is 3-8 molar parts, the Mg element is 1-3 molar parts, and the Mn element is 0.1-1 molar parts.
5. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 1, characterized in that, The secondary component also includes a fourth secondary component, a glass phase, and the amount of the glass phase is 0.2 to 5 parts by mass, based on 100 parts by mass of the main component powder. The glass phase is selected from one or more of the Ba-B-Si system, Ba-B-Si-Al system, Li-Al-Ti-Si system, or Ba-Ca-Si system.
6. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 5, characterized in that, Based on 100 parts by mass of the main component powder, the amount of the glass phase is 0.2 to 3 parts by mass.
7. The high-entropy energy storage ceramic composition suitable for base metal electrodes according to claim 1, characterized in that, The Gd may be partially or completely replaced by one or more of Y, Dy, Ho, Er, Yb, La, Nd, and Sm.
8. A method for preparing a high-entropy energy storage ceramic composition suitable for base metal electrodes as described in any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Weigh the main component raw materials and auxiliary component raw materials according to the design ratio. The main component raw materials include compounds that provide A-site cations Ba, Ca, and Sr, and compounds that provide B-site cations Ti and Zr. The auxiliary component raw materials include compounds that provide Gd, compounds that provide Mg, and compounds that provide Mn. When it is necessary to add the glass phase, the glass phase powder is also weighed out; (2) Place the weighed raw materials in a dispersion medium and mix them by wet ball milling or sand milling; (3) After drying, pre-calcined at 1050-1200℃ for 1-4 hours to form a high-entropy perovskite solid solution; (4) The pre-calcined powder is ball-milled twice, a binder is added, and then dried and granulated; (5) The granulated powder is shaped into a green body; (6) Degumming; (7) Sintering is carried out in a reducing atmosphere at 1180-1230℃ for 1-4 hours; (8) Under the condition that the oxygen partial pressure is higher than the reducing atmosphere of step (7), the re-oxidation treatment is carried out at 800-1050°C for 0.5-4 hours.
9. The preparation method according to claim 8, characterized in that, The reducing atmosphere in step (7) is N2-H2-H2O or N2-H2 mixture, and its oxygen partial pressure matches the Ni / NiO equilibrium oxygen partial pressure.
10. The preparation method according to claim 8, characterized in that, The molding process in step (5) is dry pressing, casting, lamination, or isostatic pressing.